Focus on TILs: Prognostic significance of tumor infiltrating lymphocytes in human melanoma - Oble, Darryl A. (Academy of Cancer Immunology, 2009)
Tumors contain variable numbers of lymphocytes, referred to as tumor infiltrating lymphocytes (TILs). In melanoma, the intensity of this lymphocytic infiltrate is believed to correlate with outcome, though there is some debate about the applicability of this finding for all melanomas. Much research has gone into classifying TILs with respect to antigen receptor structure and the antigen to which melanoma-specific T cells react. However, these studies for the most part did not immunophenotype TILs, and recent data has revealed that the composition of tumoral lymphocytes is not homogenous, but rather represents varying contributions from many lymphocytic subsets. Furthermore, the function of TILs is often compromised as a result of the accumulation of immunoregulatory cells and various tumor escape mechanisms. These recent insights stress the need to collect more data on the composition and function of TIL infiltrates before definitive conclusions about the prognostic significance of TILs can be drawn. Advances in immunology have also facilitated the development of immunotherapeutic strategies, examples of which will be discussed with a special emphasis on blocking antibodies against CTLA-4, which are prototypical immunotherapeutic agents. This flurry of novel "biological" therapies will undoubtedly complicate our already incomplete understanding of TIL immunobiology as each of these agents has the potential to uniquely distort the series of immunological events which normally occur in untreated melanoma. Therefore, considerable research is needed to better elucidate the function and prognostic significance of TILs in both untreated melanoma and tumors treated with "biological" therapy.